Drinking patterns among Finns aged 60 years and over from the 1990s onwards. Issue 5 (October 2020) - Tigerstedt, Christoffer; Härkönen, Janne; Mäkelä, Pia; Parikka, Suvi; Vilkko, Anni
Aim: To analyse prevalence and trends in older people's (60+) alcohol use in Finland in 1993–2018. Data and method: Data on people aged 65+ were obtained from the Health Behaviour and Health among the Finnish Elderly study (HBHFE) for the years 1993–2011 and from its successor the National FinSote Survey for the years 2013–2018. Data for 60–64-year-olds and for the reference group (20–59-year-olds) were obtained from the Health Behaviour and Health among the Finnish Adult Population (HBHFA) study for the years 1993–2011 and from the FinSote study for the years 2013–2018. Four measures were chosen to describe prevalence and trends in drinking patterns in five-year age groups among men and women aged 60+: prevalence of current drinking, prevalence of frequent drinking, typical amounts of drinking and prevalence of heavy episodic drinking (HED). Results: Regarding prevalence of current drinking and frequent drinking, older women have been catching up with men, but older men still consume larger amounts of alcohol per occasion. The long-lasting increase in the prevalence of current drinkers continued in most older female age groups into the 2010s, settled in most older male and some female age groups, and shifted downwards in the oldest male age groups. In most older male and female age groups, the increasing trend in frequent drinking continued to the present. Data on typical amounts consumed and HED were only available for 2013–2018. In that period those measures remained rather stable. Conclusion: More detailed research on drinking patterns among people aged 60+ years is needed for two reasons: older people's drinking is a new cultural phenomenon and alcohol-related social and health harms are increasing in older age groups.